The thrill of it all! [videorecording (DVD)] - Jewison, Norman, 1926-; Day, Doris, 1922-2019-; Garner, James. 1928-2014; Francis, Arlene; Andrews, Edward, 1914-1985; Reiner, Carl, 1922-2020- (MCA/Universal Home Video, 2002)
A doctor's peaceful domestic life is turned upside down when his restless spouse becomes famous doing television commercials.